ANALISIS KUALITAS CANVA SEBAGAI PLATFORM DESAIN ONLINE DAN MEDIA PEMBELAJARAN INTERAKTIF - Ari Susanto, Agus; Kriya Almanfaluti, Istian (Jurnal Teknologi Komputer dan Informatika, 2025)
This study aims to analyze the quality of Canva as an online design platform utilized in interactive learning, with a Systematic Literature Review (SLR) approach and using the WebQual 4.0 framework. Five relevant scientific articles were selected based on inclusion and exclusion criteria, then reviewed based on three main dimensions: usability, information quality, and service interaction quality. The results of the analysis show that Canva has a high level of usability, offers a charming and user-friendly interface. In addition, the quality of information is considered good because Canva provides various templates and educational design elements that support understanding of the material. However, the quality of service interaction is still relatively less than optimal, especially in the context of bold collaboration and interaction systems. Overall, Canva has proven effective in increasing student engagement and supporting creative visual learning processes. This study recommends improving user training and integrating Canva with digital learning systems so that users.